2012
DOI: 10.2310/jim.0b013e318254519e
|View full text |Cite
|
Sign up to set email alerts
|

RANTES, TNF-α, Oxidative Stress, and Hematological Abnormalities in Hepatitis C Virus Infection

Abstract: The data support the concept of chemokines (RANTES) as mediators of liver cell injury in HCV infection. In addition, MDA and NO levels might be used as monitoring markers for oxidative stress in hepatitis C infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Earlier study reported that infections are likely associated with oxidative stress in a number of ways. 13 In our study we found the severity of oxidative stress was more prominent among the CF-VAD patients with infection indicating the active involvement of oxidative stress in this process.…”
Section: Discussionsupporting
confidence: 52%
“…Earlier study reported that infections are likely associated with oxidative stress in a number of ways. 13 In our study we found the severity of oxidative stress was more prominent among the CF-VAD patients with infection indicating the active involvement of oxidative stress in this process.…”
Section: Discussionsupporting
confidence: 52%
“…Concentration of chemokine Rantes is higher in HBV infected patients than in the controls [18]. Besides, significant increases of the levels of Rantes, TNF-a, and NO in Hepatitis C virus-infected patients are observed [19]. Another study has shown that MCP-1 plasma levels are higher in both alcoholic liver disease and alcoholic hepatitis patients than in the controls, and alcoholic hepatitis patients have significantly higher hepatic expression of MCP-1 [20].…”
Section: Discussionmentioning
confidence: 82%
“…Chronic HCV infection is associated with production of the pro-inflammatory cytokine TNFα in vivo [46], [47]. Furthermore, TNFα is an important regulatory factor in HIV pathogenesis and acts through NF-kB to activate HIV transcription [18], [56].…”
Section: Resultsmentioning
confidence: 99%
“…HCV also has several immunoregulatory effects on the host that influence pathogenicity and may facilitate interactions with the HIV promoter. For example, tumor necrosis factor alpha (TNFα), a monocyte/macrophage-derived pro-inflammatory cytokine, is elevated during chronic HCV infection but also plays a pivotal role in HIV pathogenesis by inducing viral transcription via the NF-kB pathway [18], [45][47].…”
Section: Introductionmentioning
confidence: 99%